Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2134/cftm2017.02.0014
|View full text |Cite
|
Sign up to set email alerts
|

On‐Farm Winter Wheat Response to Nitrogen‐, Phosphorus‐, Potassium‐, and Sulfur‐Rich Strips in Oklahoma

Abstract: Temporal and spatial variations both play a major role in nutrient requirements and availability. This study was conducted to highlight variability in nutrient requirements across landscapes, soil types, and environments, and to evaluate if Oklahoma producers' current fertilization management schemes for nitrogen (N), phosphorus (P), potassium (K), and sulfur (S) are maximizing winter wheat (Triticum aestivum L.) grain yields. Nutrient-rich strips of N, P, K, and S and a farmer-practice strip were established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
2
Order By: Relevance
“…The effect of sulphur applied with nitrogen during the vegetation was therefore insignificant. This correlates with other published results [ [67] , [68] , [69] , [70] , [71] ], even if the increasing yield after the N + S application is often discussed. The non-significant result of co-application of N and S can be possibly explained by the relatively low S requirement of wheat and its late application in the BBCH 30–32.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of sulphur applied with nitrogen during the vegetation was therefore insignificant. This correlates with other published results [ [67] , [68] , [69] , [70] , [71] ], even if the increasing yield after the N + S application is often discussed. The non-significant result of co-application of N and S can be possibly explained by the relatively low S requirement of wheat and its late application in the BBCH 30–32.…”
Section: Discussionsupporting
confidence: 92%
“…Variability in climate and environment across the state of Oklahoma presents issues with accurately depicting and replicating producers’ conditions on the limited amount of university‐managed research areas. Although researchers aim to manage research fields spatially, studies have shown that on‐farm studies will allow meaningful data collection for a given region (Abit et al., 2017; Kyveryga et al., 2018). To conduct research across a range of highly varied soil nutrient status, studies were established and harvested across Oklahoma at 23 and 26 on‐farm locations in the 2016 and 2017 growing seasons, respectively, with no repeated locations.…”
Section: Methodsmentioning
confidence: 99%
“…До важливих агрохімічних показників родючості ґрунту поряд з гумусом належать вміст азоту, фосфору і калію. Вплив цих елементів живлення на врожайність сільськогосподарських культур на різних типах ґрунтів та стадіях росту рослин, а також трансгенні підходи до підвищення ефективності їхнього засвоєння розглядаються в багатьох працях (Abit et al, 2017;Anh, 2017;Teng, 2017).…”
Section: вступunclassified
“…Така сама закономірність реєструється й у показниках умісту гумусу. З низькими показниками азоту пов'язана і невисока продуктивність культур, що підтверджують і праці Abit et al (2017), Anh (2017), тому застосування азотних добрив є обов'язковим.…”
Section: обговоренняunclassified